Effects of Different Doses of Systemic Isotretinoin on Eyes: A Histopathological and Immunohistochemical Study in Rats. Issue 5 (May 2020) - Karadag, Remzi; Karadag, Ayse Serap; Ozlu, Emin; Oguztuzun, Serpil; Simsek, Gulcin Guler; Esmer, Oktay; Onder, Sevda; Bilgili, Serap Gunes
Abstract : Purpose: To evaluate ocular side effects associated with systemic isotretinoin histopathologically. Methods: In this multicenter study, a total of 15 male and 15 female rats were randomly divided into 3 equal groups according to the oral dose of isotretinoin they were administered: 0 mg/kg/d (group A), 7.5 mg/kg/d (group B), and 15 mg/kg/d (group C). Biopsy specimens were taken from the globe conjunctiva, cornea, and eyelid conjunctiva. Expression levels of human beta-defensin-1, human beta-defensin-2, toll-like receptor (TLR)-2, and TLR-4 were evaluated by immunohistochemical methods. Results: The number of goblet cells in eyelid conjunctiva was significantly lower in group B than that in group A and group C ( P = 0.002). The sizes of meibomian gland acini were significantly smaller in group B and group C than those in group A ( P < 0.001). Fibrosis of eyelid conjunctiva was significantly higher in group C and group B than that in group A ( P = 0.002). The levels of staining of TLR-4 in the cornea with group B were significantly lower compared with group C ( P = 0.035). Conclusions: Our study suggests that isotretinoin in the early period affects eyelid conjunctiva and meibomian glands without affecting the globe conjunctiva and cornea. Occurrence of the initial symptoms of isotretinoin on the eyelids, especially on the meibomian glands, suggests that the symptoms of patients occur because of evaporative dry eye.